PENGUJIAN EFEK MODERASIAN E-GOVERNMENT PADA HUBUNGAN ICT DEVELOPMENT DAN MOBILE PAYMENT DENGAN LEVEL KORUPSI DI NEGARA MAJU DAN NEGARA BERKEMBANG - Eri Kartika; Darlin Aulia (Politeknik Negeri Ambon, 2023)
Several studies have stated that ICT development, mobile payments, and e-government have an impact on corruption, although other studies say they have no effect on corruption. This study aims to analyze the impact of ICT development and mobile payment with or without e-government moderation on the corruption index in developed and developing countries. This study also adds control of corruption data as a control variable. Researchers used the cross-section method to process data samples consisting of 59 developed countries and 72 developing countries. The approach used is a quantitative approach, and the data used are secondary data published in 2017 and 2018. The results show that there is a significant influence between ICT development, mobile payment, and e-government moderation on corruption in developed countries. Meanwhile in developing countries, the significant influence is only shown by ICT development towards corruption without e-government moderation. This study only focuses on corruption in the public sector in developed and developing countries.